ANALISIS LOGAM BERAT Cu DAN Cd PADA SEDIMEN DI SEKITAR PERAIRAN LAUT DANGKAL SELAT BUTON KAB. MUNA - Wa Ode Rustiah (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2015)
A research has been conducted to determine the contents of heavy metals Cu and Cd in the sediment of shallow sea water Buton Strait, Muna by using Atomic Absorption Specthrofotometric instrument. The results show that average contents of these metals in mg/Kg of dry sediment are Cu = 4,3 mg/Kg and Cd = 24,4 mg/Kg respectively. These results of Cu metal are lower than the threshold value that could given effect according to the manual of sediment quality from Febris and Werner,(1994), but results of Cd metal could be concluded that the values would be approach to the refference values. In other words, coastal environmental quality with the heavy metal in critical condition, until the special handle would be needed for reducing the accused of the metals.